1999
DOI: 10.1002/(sici)1096-9918(199908)28:1<155::aid-sia596>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and reactivity of α-Al2O3-supported Pt-Co bimetallic catalysts

Abstract: Bimetallic Pt–Co and monometallic Pt and Co catalysts in as‐prepared and reduced states were characterized by X‐ray diffraction, temperature‐programmed reduction, XPS and Farier transform infrared spectroscopy (FTIR). Temperature‐programmed reduction and XPS results showed that the addition of platinum lowered the reduction temperature of cobalt oxides and simultaneously increased the amount of cobalt surface phase. The metallic Pt and Co in bimetallic Pt–Co catalysts was found to be highly dispersed in suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…102 The existence of Co-Pt interactions in these catalytic systems was further confirmed by Tang et al making use of IR with CO as probe molecule. 104 The results suggested that there was a strong interaction between Pt and Co atoms. Very recently, Jacobs et al have reported on Co-Pt/Al 2 O 3 catalysts investigated by EXAFS at the Pt L-edge, and they concluded that isolated Pt atoms interact with the supported cobalt clusters without forming Pt-Pt bonds.…”
Section: Platinummentioning
confidence: 99%
“…102 The existence of Co-Pt interactions in these catalytic systems was further confirmed by Tang et al making use of IR with CO as probe molecule. 104 The results suggested that there was a strong interaction between Pt and Co atoms. Very recently, Jacobs et al have reported on Co-Pt/Al 2 O 3 catalysts investigated by EXAFS at the Pt L-edge, and they concluded that isolated Pt atoms interact with the supported cobalt clusters without forming Pt-Pt bonds.…”
Section: Platinummentioning
confidence: 99%
“…For gas-to-liquid (GTL) technology, cobalt catalysts are considered promising [1,2] due to their low water-gas shift (WGS) activity. On the other hand, Fe-based catalysts are often employed for coal-derived syngas, since the intrinsic WGS activity is Pt, and Re [4,[13][14][15][16][17][18][19][20][21][22][23] are often employed to facilitate the reduction of cobalt species interacting with the support and thereby generate more available active cobalt metal surface sites to participate in synthesis.…”
Section: Introductionmentioning
confidence: 98%
“…[21][22][23][24][25] Due to their bimetallic nature, additional degrees of complexity can arise as the two components might interact differently with the plasma.…”
Section: Introductionmentioning
confidence: 99%